REGγ Contributes to Regulation of Hemoglobin and Hemoglobin δ Subunit. (16th July 2017) - Zuo, Qiuhong; Cheng, Shanshan; Huang, Wenxiang; Bhatti, Muhammad Zeeshan; Xue, Yanyan; Zhang, Yuanyuan; Zhang, Bianhong; Li, Lei; Wu, Lin; Fu, Junjiang; Chen, Jiwu; Li, Xiaotao
Abstract : Hemoglobin (Hb) is a family of proteins in red blood cells responsible for oxygen transport and vulnerable for oxidative damage. Hemoglobin δ subunit (HBD), a member of Hb family, is normally expressed by cells of erythroid lineage. Expression of Hb genes has been previously reported in nonerythroid and hematopoietic stem cells. Here, we report that Hb and HBD can be degraded via REG γ proteasome in hemopoietic tissues and nonerythroid cells. For this purpose, bone marrow, liver, and spleen hemopoietic tissues from REGγ +/+ and REGγ −/− mice and stable REG γ knockdown cells were evaluated for the degradation of Hb and HBD via REG γ . Western blot and immunohistochemical analyses exhibited downregulation of Hb in REG γ wild-type mouse tissues. This was validated by dynamic analysis following blockade of de novo synthesis of proteins with CHX. Degradation of HBD only occurred in REG γ WT cells but not in REG γ N151Y, a dominant-negative REG γ mutant cell. Notably, downregulation of HBD was found in HeLa shN cells with stimulation of phenylhydrazine, an oxidation inducer, suggesting that the REG γ proteasome may target oxidatively damaged Hbs. In conclusion, our findings provide important implications for the degradation of Hb and HBD in hemopoietic tissues and nonerythroid cells via the REG γ proteasome.